An Analysis of Imagery in a Collection of Poems by Laksmi Pamuntjak in Goenawan Mohamad's Poetry - Julyanta Br Sitepu; Sarah Rahma Fauziah; Abdul Muhid Murtadho (STIBA IEC JAKARTA, 2026)
This study analyses both the difficulties and achievements involved in translating Goenawan Mohamad’s modern lyric poetry, which is known for its philosophical richness, compact diction, and ambiguity. It focuses on sensory imagery as a key element in shaping readers’ experiences and evaluates how effective the translator, Laksmi Pamuntjak, maintains aesthetic equivalence—balancing poetic form and meaning—when rendering imagery in the target language. This study uses a Qualitative Descriptive Method with a Text-Based Comparative Study design, analyzing 80 units of imagery. The results of the study show that all seven types of sensory imagery (Visual, Auditory, Tactile, Kinesthetic, Gustatory, Olfactory, and Organic) appear in the translations, confirming the achievement of a complete sensory spectrum. The key findings are the strong dominance of Visual Imagery with 36 occurrences and Kinesthetic Imagery with 31 occurrences.